2023
DOI: 10.1186/s40164-023-00419-w
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin promotes tumor angiogenesis and progression of non-small-cell lung cancer by elevating WISP3 expression via FAK/MAPK/ HIF-1α axis and activating wnt signaling pathway

Abstract: Background Fibronectin, an extracellular matrix protein, has been reported to be associated with heterogeneous cancer stemness, angiogenesis and progression in multiple cancer types. However, the roles and the underlying mechanism of fibronectin on the progression NSCLC need to be further elucidated. Methods Public dataset such as Kaplan-Meier Plotter was used to determine the prognostic significance of genes. The correlation of different protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Angiogenesis is one of the hallmarks of cancer and blood vessels are also the important components of the TME [ 11 , 27 ]. Notably, previous evidence showed that FAK pathway was associated with angiogenesis and tumor growth [ 28 30 ]. Therefore, we questioned whether the use of FAK inhibitor has an impact on TME via inhibiting tumor angiogenesis in KL tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis is one of the hallmarks of cancer and blood vessels are also the important components of the TME [ 11 , 27 ]. Notably, previous evidence showed that FAK pathway was associated with angiogenesis and tumor growth [ 28 30 ]. Therefore, we questioned whether the use of FAK inhibitor has an impact on TME via inhibiting tumor angiogenesis in KL tumors.…”
Section: Resultsmentioning
confidence: 99%
“… 40 , 41 In lung cancer, FN expression is abnormal, especially in non‐small cell lung cancer. 42 , 43 Moreover, recent evidence suggests that VM formation is frequently observed in ECM‐rich regions containing large amounts of proteins such as collagen and FN. 44 Consistent with the properties of matrix, alteration in collagen and FN concentration may directly impact cellular behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that the activation of MAPK1 was linked to promoting paclitaxel-based chemotherapy resistance in breast cancer [29,30]. It was also reported that MAPK/ERK signaling pathway could stimulate the accumulation of HIF-1α to promote NSCLC progression [31]. Therefore, these previous ndings provide us a consideration that activated MAPK/ERK pathway might enhance HIF-1α expression to drive Linc01436 overexpression which provokes Ras/Raf/ERK signaling pathway leading to poor response of NAC for breast cancer patients.…”
Section: Discussionmentioning
confidence: 96%